2003
DOI: 10.1139/z03-070
|View full text |Cite
|
Sign up to set email alerts
|

Rapid female multiple mating in red flour beetles (Tribolium castaneum)

Abstract: Many female insects mate with multiple males within a single fertile period despite costs such as expenditure of energy and time and contraction of sexually transmitted diseases. In the red flour beetle, Tribolium castaneum, females remate with different males within minutes of the first copulation. If rapid multiple mating is adaptive then multiply mated females should have higher fitness than singly mated females. In this study, we determined the remating frequency of female beetles, characterized female mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 50 publications
1
29
1
Order By: Relevance
“…However, studies showing a lack of benefits to females are also emerging from experimental data for other organisms. Examples include frogs (45,46), newts (47), beetles (48,49), and mites (50). Instead of benefits, these often show significant costs to females (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies showing a lack of benefits to females are also emerging from experimental data for other organisms. Examples include frogs (45,46), newts (47), beetles (48,49), and mites (50). Instead of benefits, these often show significant costs to females (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, greater productivity of clonal mixtures of the alga Chlamydomonas reindhartii was explained by the presence of a highly productive clone that quickly dominated the population (Bell 1991). Mating in Tribolium castaneum occurs rapidly and multiple times after sexual maturity (Pai and Yan 2003); hence, most adults used to initiate the experimental populations had probably already mated within their parent stock population. Thus, eggs in the experimental populations would largely carry strain-specific allele combinations, and the next generation could have a higher representation of more fecund strains, allowing their alleles to rapidly increase in Note: Results of Tukey HSD pairwise contrasts are given for all single-strain and four-strain (All) populations in each habitat, along with the difference in the mean response of each single-strain and four-strain combination.…”
Section: Nonadditive Effects In the Ancestral Habitat: Selective Sweepsmentioning
confidence: 99%
“…These include higher larval viability of offspring (Pai et al 2005; but see Pai and Yan 2003b), higher insemination success of sons (Pai and Yan 2002b), and higher egg viability in grand-offspring (Pai and Yan 2002b). A recent study has also found significant father-son heritability for sperm offense, reproductive success, and longevity (Lewis et al 2012), suggesting that females could benefit from mate choice.…”
Section: Benefits and Costs Of Female Polyandrymentioning
confidence: 99%
“…They can also store and use sperm from a single mating for up to four months, laying over 700 fertile eggs during this period (Bloch Qazi et al 1996). Despite such abilities, these females appear to be continuously receptive, mating with up to 12 different males per hour in various experimental settings (Park 1933;Sokoloff 1974;Pai and Yan 2003b;Pai et al 2007). Even though these are probably overestimates due to most studies using previously isolated males having unlimited access to virgin females, T. castaneum natural mating rates are still extremely high (Wool 1967) and must be explained by some other net benefits besides sperm replenishment.…”
Section: Benefits and Costs Of Female Polyandrymentioning
confidence: 99%